Stable High‐Pressure Methane Dry Reforming Under Excess of CO2. Issue 23 (11th September 2020) - Ramirez, Adrian; Lee, Kunho; Harale, Aadesh; Gevers, Lieven; Telalovic, Selvedin; Al Solami, Bandar; Gascon, Jorge
Abstract: Dry reforming of methane (DRM), the conversion of carbon dioxide and methane into syngas, offers great promise for the recycling of CO2 . However, fast catalyst deactivation, especially at the industrially required high pressure, still hampers this process. Here we present a comprehensive study of DRM operation at high pressure (7–28 bars). Our results demonstrate that, under equimolar CH4  : CO2 mixtures, coke formation is unavoidable at high pressures for all catalysts under study. However, under substoichiometric CH4  : CO2 ratios (1 : 3), a stable high pressure operation can be achieved for most catalysts with no sign of deactivation for at least 60 hours at 14 bars, 800 °C and 7500 h −1 . In addition to the enhanced stability, under these conditions, the amount of CO2 abated per mol of CH4 fed increases by a 50 %. Abstract : Towards High‐Pressure Methane Dry Reforming . The conversion of both CO2 and CH4 greenhouse gases via dry methane reforming (DRM) could provide an environmentally friendly route for the synthesis of valuable chemicals. However, to achieve the final industrial application, research at high pressure feeds is still required. In this work we have explored the DRM reaction at high pressure via a comprehensive high‐throughput screening on 6 different industrial catalysts. Our results demonstrate the enormous challenges of stable DRM performance under these high pressure conditions. Nevertheless, we have also found that with the use of substoichiometric CH4  : CO2 reactant ratios (i. e. 1 : 3) stable high pressure operation can be achieved for most catalysts with no sign of deactivation.